2020
DOI: 10.1088/2399-6528/ab7abd
|View full text |Cite
|
Sign up to set email alerts
|

Negative differential resistance effect of blue phosphorene-graphene heterostructure device

Abstract: We report on the electrical transport properties of new graphene/blue phosphorene heterostructure devices by density functional theory (DFT) within the non-equilibrium Green's function (NEGF) approach. From the results, it is found that the devices with different length of contacts layers show semiconducting nature. The integrated contacted length of graphene/blue phosphorene two-layer device shows the best conductivity under a bias voltage. The negative differential resistance effect (NDR) is also found in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…5–8 A notable phenomenon of spin caloritronics is the spin Seebeck effect (SSE), 9–12 which can generate net spin current from the temperature gradient, and can decrease the dissipation heat caused by the total charge current. Meanwhile, a lot of spintronic effects such as the spin-filter, 13 spin-valve, 14 spin rectification, 15 magnetoresistance 16 and NDR effect 17 have been utilized to produce next-generation electronic devices.…”
Section: Introductionmentioning
confidence: 99%
“…5–8 A notable phenomenon of spin caloritronics is the spin Seebeck effect (SSE), 9–12 which can generate net spin current from the temperature gradient, and can decrease the dissipation heat caused by the total charge current. Meanwhile, a lot of spintronic effects such as the spin-filter, 13 spin-valve, 14 spin rectification, 15 magnetoresistance 16 and NDR effect 17 have been utilized to produce next-generation electronic devices.…”
Section: Introductionmentioning
confidence: 99%
“… 9 , 16 , 18 , 19 In particular, zigzag-edged graphene nanoribbons (ZGNRs) are more notable because of its spin-resolved electronic and transport properties. 20 23 At present, a lot of spintronic and spin caloritronic devices based on ZGNRs are realized in theoretical and experimental studies, 24 , 25 and even the spin Seebeck effect also has been found in ZGNRs. 9 , 18 , 26 However, it is worth noting that graphene is able to form nanosize bubbles by trapping gas molecules under high pressure 27 , 28 or growing in ultrahigh vacuum.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, graphene nanoribbons (GNR), which exhibit various spintronic and thermoelectric properties, have attracted much attention and are one of the most promising candidate materials for future electronic devices. ,,, In particular, zigzag-edged graphene nanoribbons (ZGNRs) are more notable because of its spin-resolved electronic and transport properties. At present, a lot of spintronic and spin caloritronic devices based on ZGNRs are realized in theoretical and experimental studies, , and even the spin Seebeck effect also has been found in ZGNRs. ,, However, it is worth noting that graphene is able to form nanosize bubbles by trapping gas molecules under high pressure , or growing in ultrahigh vacuum . Theoretically, the presence of the graphene nanobubble may cause elastic strain and modification on electron density, affecting the electron-hopping amplitude between carbon atoms .…”
Section: Introductionmentioning
confidence: 99%